The Learning of Mathematics Based on Individual Differences : A Topic Trend Bibliometric Analysis Using VOSviewer - M.J. Dewiyani Sunarto; Julianto Lemantara (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to establish a foundation for the development of differentiated learning through an analysis of trends in articles related to personality type differences in the field of mathematics education. The research method used was descriptive, using Bibliometric Analysis. These 422 data from Scopus have been from Scopus-indexed journals and were obtained by defining search keywords, namely "individual differences." These articles were then filtered based on the highest citation, resulting in 100 articles that were analyzed using Vos Viewer and Microsoft Excel to display the necessary data for analysis. The results of this study indicated that from many articles that had been analyzed, individual differences have a wide meaning, it could be gender, characteristics, thinking process, fear, attitude, and others. Those differences should be taken into consideration by the teacher and cannot be neglected because they can influence the learners. From the data that has been analyzed, the topic above has been increasing after 2017 with the United States and the United Kingdom as the most recent country that published this topic. Cognition is the journal that has the most publications on this topic, with Engle, R. W. as the most productive writer. The most trending article was about Mathematics in general, mathematics concepts, and the phenomena in teaching and learning math. The next piece of advice is about the development of the individual learning model, its evaluation, and its utilization in creating a differentiated learning model.